2018
DOI: 10.1016/j.ram.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and phylogenetic analysis of human papillomavirus infection in women with cervical lesions and cancer from the coastal region of Ecuador

Abstract: The aim of the present study was to gather information regarding the molecular epidemiology of Human papillomavirus (HPV) and related risk factors in a group of women with low- and high-grade cervical lesions and cancer from the coastal region of Ecuador. In addition, we studied the evolution of HPV variants from the most prevalent types and provided a temporal framework for their emergence, which may help to trace the source of dissemination within the region. We analyzed 166 samples, including 57 CIN1, 95 CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
2
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 40 publications
2
9
2
16
Order By: Relevance
“…Of the 144 participants recruited in this study 16.9% were positive for HPV type 16, which is slightly higher than the study carried out in Kano, Nigeria where they reported prevalence of 15.8% for HPV type 16, though their study recruited lesser subjects (50) than this study [13]. A study carried out in Lagos, Nigeria, which they reported HPV type 16 to be 46.9%, this is not in accordance with the present study [20], another study reported 23.5% [21], while in a study carried out in the south western Nıgeria HPV 16 prevalence (3.5%) was very low than the one in this study [22]. with P value of 0.14 [24].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Of the 144 participants recruited in this study 16.9% were positive for HPV type 16, which is slightly higher than the study carried out in Kano, Nigeria where they reported prevalence of 15.8% for HPV type 16, though their study recruited lesser subjects (50) than this study [13]. A study carried out in Lagos, Nigeria, which they reported HPV type 16 to be 46.9%, this is not in accordance with the present study [20], another study reported 23.5% [21], while in a study carried out in the south western Nıgeria HPV 16 prevalence (3.5%) was very low than the one in this study [22]. with P value of 0.14 [24].…”
Section: Resultscontrasting
confidence: 99%
“…This study shows there is an association between infection with HPV 16 and cervical lesions, this is consistent with a study where the strength of the association was even demonstrated with odd ratio of 182, showing a strong association between HPV 16 and cervical lesions[23]. While another study also showed HPV 16 is a strong risk factor for cervical lesion[21].Symptoms such as genital itching, vaginal discharge (also known PV discharge), post-coital bleeding, are the most common symptoms seen in women with cervical abnormalities and vaginal infections. There was no complain of post-coital bleeding among the participants in this study, but all the subjects that were positive for HPV type 16 complained of either genital…”
supporting
confidence: 91%
“…De acuerdo con los pocos estudios realizados en América del Sur, además del VPH 16 y el 18, el VPH 58 es otro de los VPH-AR encontrados con mayor frecuencia en la región. Este último ha sido detectado en el centro y norte de Brasil, Argentina, Colombia y Ecuador 5 .…”
Section: Introductionunclassified
“…The objective of this study is to show the prevalence of HPV genotypes in Ecuadorian mestizo women [13], in comparison with other studies at Latin America [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (see table 3).…”
Section: Introductionmentioning
confidence: 99%